Analysis of Students Metacognition Ability through Problem Based Learning Assisted by Worksheets on Environmental Pollution Material - Ummayah, Fivi Fari Dhotul; Dewi, Novi Ratna (Journal of Environmental and Science Education, 2021)
Metacognition ability is important for students to be able to organize and examine their thinking processes. In fact, the seventh-grade students of SMP Negeri 13 Semarang do not yet know their metacognitive abilities and teachers have not deliberately built students' metacognitive abilities in various lessons with certain strategies. Problem-based learning (PBL) has the potential to build students' metacognitive abilities. This study aims to analyze the profile of students' metacognitive abilities through PBL assisted by environmental pollution worksheets. This research is a mixed-method approach which refers to Sugiono with a sequential explanatory strategy. Quantitative data were obtained through tests, while qualitative data were obtained through a metacognition ability questionnaire. The sample used was class VIIB and was selected by purposive sampling. The results based on the test analysis showed that the VIIB students had the most level 3 metacognition ability with a percentage of 54% and based on a questionnaire reach 76%. Students with the level 3 metacognition ability are able to develop their thinking processes and have poor analytical power. Students with level 1 and level 2 metacognition abilities have not been able to develop their thinking processes and have poor analytical power. Students with level 4 and level 5 metacognition abilities are able to develop their thinking processes and have good analytical power. Student's responses analysis about PBL assisted by worksheets are in a good category. Learning with the right method is needed in building and developing students' metacognitive abilities for the better.